Curcumin Combined with Thalidomide Reduces Expression of STAT3 and Bcl-xL, Leading to Apoptosis in Acute Myeloid Leukemia Cell Lines - Mohammadi Kian M; Salemi M; Bahadoran M; Haghi A; Dashti N; Mohammadi S; Rostami S; Chahardouli B; Babakhani D; Nikbakht M (Dove Medical Press, 2020)
Mahnaz Mohammadi Kian, 1, 2 Mahdieh Salemi, 1, 2 Mohammad Bahadoran, 3 Atousa Haghi, 1, 4 Nasrin Dashti, 5 Saeed Mohammadi, 1, 2 Shahrbano Rostami, 1, 2 Bahram Chahardouli, 1, 2 Davood Babakhani, 1 Mohsen Nikbakht 1, 2 1Hematology Oncology and Stem Cell Transplantation Research Center, Tehran University of Medical Sciences, Tehran, Iran; 2Hematologic Malignancies Research Center, Tehran University of Medical Sciences, Tehran, Iran; 3Department of Biochemistry, Institute of Biochemistry and Biophysics, University of Tehran, Tehran, Iran; 4Young Researchers & Elite Club Tehran Medical Sciences, Islamic Azad University, Tehran, Iran; 5Department of Medical Laboratory Sciences, School of Allied Health Sciences, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Mohsen NikbakhtHematology, Oncology and Stem Cell Transplantation Research Center, Tehran University of Medical Sciences, Tehran, IranTel +982184902639Fax +982188004140Email m-nikbakht@sina.tums.ac.irNasrin DashtiDepartment of Medical Laboratory Sciences, School of Allied Health Sciences, Tehran University of Medical Sciences, Tehran, IranTel +989123583690Email dashti@tums.ac.irIntroduction: Acute myeloid leukemia (AML) is a type of blood disorder that exhibits uncontrolled growth and reduced ability to undergo apoptosis. Signal transducer and activator of transcription 3 (STAT3) is a family member of transcription factors which promotes carcinogenesis in most human cancers. This effect on AML is accomplished through deregulation of several critical genes, such as B cell lymphoma-extra-large (BCL-XL) which is anti-apoptotic protein. The aim of this study was to evaluate the effect of curcumin (CUR) and thalidomide (THAL) on apoptosis induction and also the alteration of the mRNA expression level of STAT3 and BCL-XL mRNA on AML cell line compounds.Methods: The growth inhibitory effects of CUR and THAL and their combination were measured by MTT assay in U937 and KG-1 cell lines. The rates of apoptosis induction and cell cycle analysis were measured by concurrent staining with Annexin V and PI. The mRNA expression level of STAT3 and BCL-XL was evaluated by Real-Time PCR.Results: CUR inhibited proliferation and induced apoptosis in both KG-1 and U937 cells and this effect increased by combination with THAL. The expression level of STAT3 and BCL-XL was significantly down-regulated in KG-1 cells after treatment by CUR and THAL and their combination.Conclusion: Overall, our findings suggested that down-regulation of STAT3 and BCL-XL mRNA expression in response to CUR and THAL treatment lead to inhibition of cell growth and induction of apoptosis.Keywords: acute myeloid leukemia, curcumin, thalidomide, STAT3, Bcl-xL